Application of Simulation Method in Moral Learning at Lheu Mosque State Elementary School - Darniah (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to find out the application of the simulation method in the learning of morals in SDN Mesjid Lheu, Aceh Besar, as well as to evaluate its effectiveness and impact on students' moral understanding and behavior. The background of this research is based on the importance of interactive and contextual learning methods in shaping the character of students, especially in Islamic Religious Education (PAI) subjects. The method used in this research is a qualitative approach with a descriptive research type. Data collection techniques are done through observation, interviews with teachers and students, and documentation. The subjects of the research are PAI teachers and students of class V SD N Masjid Lheu Aceh Besar. The results of the research show that the simulation method can improve students' understanding of moral material, strengthen moral values, and encourage students' active participation in the learning process. Students become more enthusiastic and able to apply moral values ​​in their daily lives. Obstacles faced include limited time and students' readiness to act according to the simulation scenario. However, overall, this method is considered effective in improving the quality of moral learning.